LAMINATE, METHOD FOR PRODUCING LAMINATE, AND METHOD FOR PRODUCING FLEXIBLE ELECTRONIC DEVICE
The method addresses the challenge of achieving uniform adhesion between polyimide films and inorganic substrates by using a silane coupling agent and an aqueous medium, resulting in high-quality laminates suitable for large-area flexible electronic devices.
Patent Information
- Application Number
- JP2021551428
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-08
- Filing Date
- 2020-09-30
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2040-09-30
AI Technical Summary
The challenge lies in achieving uniform adhesion strength between polyimide films and inorganic substrates, particularly for large-area applications, while maintaining the transparency and heat resistance required for flexible electronic devices.
A manufacturing method that involves applying a silane coupling agent to the surfaces of the polyimide film and inorganic substrate, followed by the use of an aqueous medium to control the thickness of the silane coupling agent layer, ensuring uniform adhesion and minimizing blister defects.
This method allows for the production of high-quality laminates with controlled adhesion strength, reduced blister defects, and the ability to handle large-area flexible electronic devices without compromising their transparency or heat resistance.
Smart Images

Figure 0007659742000001 
Figure 0007659742000002 
Figure 0007659742000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate, a method for manufacturing a laminate, and a method for manufacturing a flexible electronic device. [Background technology]
[0002] In recent years, there has been active development of technology for forming functional elements such as semiconductor elements, MEMS elements, and display elements on polyimide films in order to make these elements lighter, smaller, thinner, and more flexible. That is, ceramics, which have heat resistance and can handle the high signal bands of information and communication devices (reaching the GHz range), have traditionally been used as the base material for electronic components such as information and communication devices (broadcasting equipment, mobile radio, portable communication devices, etc.), radar, and high-speed information processing devices. However, since ceramics are not flexible and difficult to make thin, they have the disadvantage of being limited in the fields in which they can be applied, polyimide films have recently been used as substrates.
[0003] In forming functional elements such as semiconductor elements, MEMS elements, and display elements on the surface of polyimide film, it is considered ideal to process them using the so-called roll-to-roll process, which takes advantage of the flexibility of polyimide film. However, in the semiconductor, MEMS, and display industries, process technologies have been developed for rigid flat substrates such as wafer-based or glass-based substrates. Therefore, in order to form functional elements on polyimide film using existing infrastructure, a process is used in which the polyimide film is bonded to a rigid support (inorganic substrate) made of inorganic materials such as glass plates, ceramic plates, silicon wafers, and metal plates, and then the desired elements are formed on the polyimide film and then peeled off from the support.
[0004] Incidentally, in the process of forming a desired functional element on a laminated body obtained by laminating a polyimide film and a support made of an inorganic material, the laminated body is often exposed to high temperatures. For example, in the formation of a functional element such as polysilicon or an oxide semiconductor, a process in a temperature range of about 200°C to 600°C is required. In addition, in the preparation of a hydrogenated amorphous silicon thin film, a temperature of about 200°C to 300°C may be applied to the film, and further, in order to heat and dehydrogenate the amorphous silicon to form low-temperature polysilicon, heating at about 450°C to 600°C may be required. Therefore, the polyimide film constituting the laminated body is required to have heat resistance, but as a practical problem, polyimide films that can withstand such high temperature ranges are limited. In addition, it is generally considered to use a pressure-sensitive adhesive or adhesive to laminate a polyimide film to a support, but the bonding surface between the polyimide film and the support in this case (i.e., the adhesive or adhesive for lamination) is also required to have heat resistance. However, since ordinary adhesives and adhesives for lamination do not have sufficient heat resistance, lamination using an adhesive or adhesive cannot be applied when the temperature for forming the functional element is high.
[0005] Since there are no adhesives or glues with sufficient heat resistance, the conventional technique for the above-mentioned applications is to apply a polymer solution or a polymer precursor solution onto an inorganic substrate, dry and harden the solution on the inorganic substrate to form a film for use in the application. However, the polyimide film obtained by this method is brittle and easily torn, so that the functional elements formed on the polyimide film surface are often destroyed when peeled off from the inorganic substrate. In particular, it is extremely difficult to peel off a large-area film from an inorganic substrate, and it is impossible to obtain an industrially viable yield. In view of these circumstances, a laminate of a polyimide film and an inorganic substrate has been proposed for producing a so-called flexible electronic device in which a functional element is formed on a flexible substrate, in which a polyimide film that is highly heat-resistant, tough, and thinnable is bonded to an inorganic substrate via a silane coupling agent layer, for example, a silane coupling agent (see, for example, Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 5152104 [Patent Document 2] Patent No. 5304490 [Patent Document 3] Patent No. 5531781 Summary of the Invention [Problem to be solved by the invention]
[0007] In the above-mentioned laminate, by interposing a layer containing a silane coupling agent layer between the inorganic substrate and the polyimide film, it is intended to prevent the inorganic substrate from peeling off from the polyimide film before or during device formation, and to easily peel off the inorganic substrate from the polyimide film after device formation. However, since the adhesive strength between the polyimide film and the inorganic substrate varies depending on the thickness of the silane coupling agent layer, it is extremely difficult to control the adhesive strength between the two companies to achieve a uniform adhesive strength over a large area. In addition, many heat-resistant polymers are often colored brown. This coloring is a fatal problem for display elements that control light transmission. On the other hand, for self-luminous display elements or reflective display elements, it is not a problem as long as they are used on the back side. Furthermore, for many sensors and electronic circuit elements that do not fall under the category of display elements, substrate coloring should not be a problem in itself. However, in manufacturing these electronic devices, it is essential to form a multilayer structure with a complex and precise pattern, and very precise alignment is required in the manufacturing process. In that case, if the substrate has low colorless transparency, it becomes difficult to detect the positioning mark on the back side of the substrate, and there is a problem that the method for alignment is limited. Therefore, even in cases where the display element is not a transmissive type, the substrate may be required to be colorless and transparent. Here, in particular, when a colorless polyimide is used as the polyimide film, the colorless polyimide has a higher reactivity than the colored polyimide, so the adhesive strength is likely to increase, and the tensile modulus and tensile strength are low, so the film is likely to deform during peeling, causing device damage. Therefore, when a colorless polyimide film with high transparency is used as a flexible substrate, a more advanced film thickness control technology for the silane coupling agent is required than before, and it can be said that the industrial technical difficulty is very high. That is, when attaching a colorless and highly transparent polyimide film to a large substrate in a peelable manner, it is difficult to apply a silane coupling agent layer of uniform thickness to the substrate surface. This is particularly difficult for so-called 4.5th generation glass substrates measuring 730 mm x 920 mm or more, compared to 4th generation substrates (660 mm x 800 mm), and has posed many problems in industrial production. [Means for solving the problem]
[0008] In view of the above situation, the present inventors have continued their intensive research and have found a manufacturing method that can easily control the thickness of the silane coupling agent layer to be extremely thin and uniform even in a large area exceeding the 4.5th generation size, and can obtain a high-quality laminate with few blister defects.In addition, the manufacturing method of the present invention has led to the realization of a laminate in which a colorless and highly transparent polyimide film and an inorganic substrate are laminated with an extremely homogeneous and extremely thin silane coupling agent layer, and further, it has been found that a high-quality flexible electronic device can be manufactured by using such a laminate. That is, the present invention has the following configuration. [1] A laminate having, in this order, an inorganic substrate, a silane coupling agent layer, and a polyimide film having a yellow index of 10 or less, a light transmittance at a wavelength of 400 nm of 70% or more, a tensile modulus in both the MD and TD directions of 3 GPa or more, and a CTE in both the MD and TD directions of -5 ppm / ℃ to +55 ppm / ℃, wherein the initial adhesive strength when peeling the polyimide film from the laminate by a 90 degree peeling method is 0.06 N / cm or more and 0.25 N / cm or less. [2] The laminate according to [1], characterized in that the blister defect density is 5 or less per square meter. [3] The laminate according to [1] or [2], wherein the polyimide film is rectangular, has an area of 0.65 square meters or more, and one side of the rectangle is at least 700 mm or more. [4] The laminate according to any one of [1] to [3], wherein the silane coupling agent layer is a silane coupling agent. [5] (1) applying a silane coupling agent to at least one surface of an inorganic substrate; (2) wetting either or both of the silane coupling agent-coated surface of the inorganic substrate and the adhesive surface of the polyimide film with an aqueous medium; (3) a step of laminating a polyimide film on the silane coupling agent-coated surface of the inorganic substrate; (4) a step of pressing the silane coupling agent-coated surface of the inorganic substrate and the adhesive surface of the polyimide film together while extruding the aqueous medium from between them; The method for producing a laminate according to any one of [1] to [4], characterized by having at least the following: [6] (1) applying a silane coupling agent to at least one surface of a heat-resistant polyimide film; (2) Wetting either or both of the adhesive surface of the inorganic substrate and the silane coupling agent-coated surface of the polyimide film with an aqueous medium; (3) a step of superposing a silane coupling agent-coated surface of a heat-resistant polyimide film on the inorganic substrate; (4) a step of pressing the adhesive surface of the inorganic substrate and the silane coupling agent-coated surface of the polyimide film together while extruding the aqueous medium from between them; The method for producing a laminate according to any one of [1] to [4], characterized by having at least the following: [7] A method for producing a flexible device, comprising a step of forming a functional element on a surface of the laminate obtained by the production process described in either [5] or [6] above, opposite to the adhesive surface of the polyimide film to the inorganic substrate. Effect of the Invention
[0009] As explained in the section on the prior art, in a laminate of a polyimide film for producing a flexible electronic device and an inorganic substrate such as a glass plate, it is difficult to uniformly apply a silane coupling agent layer, particularly over a large area, and as a result, it is difficult to uniformly and appropriately control the adhesive strength between the polyimide film and the inorganic substrate. However, according to the present invention, even when a colorless and highly transparent polyimide film is used, the adhesive strength can be controlled to a range of 0.06 N / cm or more and 0.25 N / cm or less, and further, blister defects are unlikely to occur between the polyimide film and the inorganic substrate, making it possible to realize a large-area laminate that is rectangular in shape with an area of 0.8 square meters and at least one side of 1 m or more. Furthermore, by using this laminate, a method for producing a large-area flexible electronic device can be provided.
[0010] In the following, to avoid complexity, the colorless and highly transparent polyimide film may be referred to simply as a polyimide film or a film, and the inorganic substrate may be referred to simply as a substrate. The present invention is the same as the conventional technology in that a silane coupling agent is applied to either a polyimide film or an inorganic substrate, and then the two are bonded (laminated). However, the present invention is significantly different in that an aqueous medium (pure water, or a mixture of water and a water-soluble solvent) is interposed between the two during lamination, and the aqueous medium is pushed out from the adhesive surfaces while laminating. By this method, excess silane coupling agent between the inorganic substrate or the polyimide film can be removed, and the amount of the silane coupling agent layer is controlled to the minimum necessary amount coordinated by affinity to the surface of at least one of the substrate and the film. It is believed that the reason why the adhesive strength between the substrate and the polyimide film changes over time or after a high-temperature process is because the reaction of the excess, unreacted silane coupling agent layer progresses. However, the method of the present invention makes it possible to remove such excess unreacted material from the adhesive interface between the substrate and the film.
[0011] Furthermore, with this bonding method, excess silane coupling agent is eliminated, making it difficult for foreign matter to be generated by condensation of reactive compounds, and at the same time, any dirt or other matter mixed in with the bonding surface is pushed out, dramatically reducing the amount of particle-sized foreign matter at the bonding interface, and as a result, reducing the number of blister defects (also known as air bubbles or floats) that are caused by these foreign matter.
[0012] According to the above-mentioned configuration, the silane coupling agent layer has a sufficient thickness and does not contain excess silane coupling agent, so the adhesive strength is not too strong, and the initial adhesive strength is in the range of 0.06 N / cm or more and 0.25 N / cm or less. This is also clear from the examples. In this regard, the inventors speculate that in the early stage of depositing the silane coupling agent on the inorganic substrate, since there are many OH groups on the surface of the inorganic substrate, these OH groups and the silane coupling agent are bonded by hydrogen bonding or chemical reaction, resulting in a strong silane coupling agent layer, but if the silane coupling agent deposition time is extended, the silane coupling agent layer, which is not necessarily bonded strongly, is likely to penetrate into the polyimide film, and the adhesive strength changes depending on the way of penetration and the way of bonding at the place where it penetrates.
[0013] In the above-mentioned configuration, it is preferable that the initial adhesive strength at 90 degrees between the polyimide film and the inorganic substrate is 0.06 N / cm or more and 0.25 N / cm or less.
[0014] When the 90 degree initial adhesive strength is 0.06 cm or more, the polyimide film can be suitably prevented from peeling off from the inorganic substrate before or during device formation. When the 90 degree initial adhesive strength is 0.25 N / cm or less, the device can be mechanically peeled off without being destroyed.
[0015] In the above-mentioned configuration, it is preferable that the number of air bubbles between the polyimide film and the inorganic substrate is 1 or less per 500 mm×500 mm.
[0016] If the number of bubbles is one or less per 500 mm×500 mm, the possibility of a device being destroyed due to bubble growth when a device is fabricated on the polyimide film can be significantly reduced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The polyimide film in the present invention is a polymer film having an imide bond in the main chain, preferably a polyimide film, a polyamideimide film, or a polyamide film, more preferably a polyimide film or a polyamideimide film, and further preferably a polyimide film.
[0018] Generally, a polyimide film is obtained by applying a polyamic acid (polyimide precursor) solution obtained by reacting diamines and tetracarboxylic acids in a solvent to a support for preparing a polyimide film, drying the solution to form a green film (also called a "precursor film" or "polyamic acid film"), and then subjecting the green film to a high-temperature heat treatment on the support for preparing a polyimide film or in a state where the green film is peeled off from the support to cause a dehydration ring-closing reaction. Alternatively, a polyimide solution obtained by a dehydration ring-closing reaction between diamines and tetracarboxylic acids in a solvent is applied to a support for preparing a polyimide film, drying the solution to form a polyimide film containing 1 to 50% by weight of solvent, and then subjecting the polyimide film containing 1 to 50% by weight of solvent to a high-temperature heat treatment and drying the polyimide film on the support for preparing a polyimide film or in a state where the polyimide film is peeled off from the support.
[0019] Generally, a polyamideimide film is obtained by applying a polyamideimide solution obtained by reacting diisocyanates with tricarboxylic acids in a solvent to a support for producing the polyamideimide film, drying the solution to form a polyamideimide film containing 1 to 50% by weight of solvent, and further treating the polyamideimide film containing 1 to 50% by weight of solvent at a high temperature on the support for producing the polyamideimide film or after peeling it off from the support and drying the film.
[0020] Generally, a polyamide film is obtained by applying a polyamide solution obtained by reacting diamines and dicarboxylic acids in a solvent to a support for producing the polyamide film, drying the polyamide film to form a polyamide film containing 1 to 50% by weight of solvent, and further drying the polyamide film containing 1 to 50% by weight of solvent at a high temperature on the support for producing the polyamide film or after peeling it off from the support.
[0021] The tetracarboxylic acids, tricarboxylic acids, and dicarboxylic acids may be aromatic tetracarboxylic acids (including their acid anhydrides), aliphatic tetracarboxylic acids (including their acid anhydrides), alicyclic tetracarboxylic acids (including their acid anhydrides), aromatic tricarboxylic acids (including their acid anhydrides), aliphatic tricarboxylic acids (including their acid anhydrides), alicyclic tricarboxylic acids (including their acid anhydrides), aromatic dicarboxylic acids, aliphatic dicarboxylic acids, and alicyclic dicarboxylic acids, which are generally used in polyimide synthesis, polyamideimide synthesis, and polyamide synthesis. Among them, aromatic tetracarboxylic acid anhydrides and alicyclic tetracarboxylic acid anhydrides are preferred, aromatic tetracarboxylic acid anhydrides are more preferred from the viewpoint of heat resistance, and alicyclic tetracarboxylic acids are more preferred from the viewpoint of light transmittance. When the tetracarboxylic acids are acid anhydrides, the anhydride structure may be one or two in the molecule, but preferably has two anhydride structures (dianhydrides). The tetracarboxylic acids, tricarboxylic acids, and dicarboxylic acids may be used alone or in combination of two or more.
[0022] Examples of aromatic tetracarboxylic acids for obtaining a colorless and highly transparent polyimide in the present invention include 4,4'-(2,2-hexafluoroisopropylidene)diphthalic acid, 4,4'-oxydiphthalic acid, bis(1,3-dioxo-1,3-dihydro-2-benzofuran-5-carboxylic acid)1,4-phenylene, bis(1,3-dioxo-1,3-dihydro-2-benzofuran-5-yl)benzene-1,4-dicarboxylate, 4,4'-[4,4'-(3-oxo-1,3-dihydro-2-benzofuran-1,1-diyl)bis(benzene-1,4-diyl)] 4,4'-[(3-oxo-1,3-dihydro-2-benzofuran-1,1-diyl)bis(toluene-2,5-diyloxy)]dibenzene-1,2-dicarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 4,4'-[(3-oxo-1,3-dihydro-2-benzofuran-1,1-diyl)bis(toluene-2,5-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-[(3-oxo-1,3-dihydro-2-benzofuran-1,1-diyl)bis(1,4-xylene-2,5-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-[4,4'-(3-oxo-1,3-dihydro-2-benzofuran-1,1-diyl)bis(toluene-2,5-diyloxy)]dibenzene-1,2-dicarboxylic acid, bis(4-isopropyl-toluene-2,5-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-[4,4'-(3-oxo-1,3-dihydro-2-benzofuran-1,1-diyl)bis(naphthalene-1,4-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-[4,4'-(3H-2,1-benzoxathiol-1,1-dioxide-3,3-diyl)bis(benzene-1,4-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-benzophenonetetracarboxylic acid, 4,4'-[(3H-2,1-benzo 4,4'-[(3H-2,1-benzoxathiol-1,1-dioxide-3,3-diyl)bis(toluene-2,5-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-[4,4'-(3H-2,1-benzoxathiol-1,1-dioxide-3,3-diyl)bis(4-isopropyl-toluene-2,5-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-[4,Examples of the tetracarboxylic acids include 4'-(3H-2,1-benzoxathiol-1,1-dioxide-3,3-diyl)bis(naphthalene-1,4-diyloxy)]dibenzene-1,2-dicarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 3,3',4,4'-diphenylsulfonetetracarboxylic acid, 3,3',4,4'-biphenyltetracarboxylic acid, 2,3,3',4'-biphenyltetracarboxylic acid, and pyromellitic acid, and their acid anhydrides. Among these, dianhydrides having two acid anhydride structures are preferred, and 4,4'-(2,2-hexafluoroisopropylidene)diphthalic dianhydride and 4,4'-oxydiphthalic dianhydride are particularly preferred. The aromatic tetracarboxylic acids may be used alone or in combination of two or more. When heat resistance is important, the aromatic tetracarboxylic acids preferably account for, for example, 50% by mass or more of the total tetracarboxylic acids, more preferably 60% by mass or more, even more preferably 70% by mass or more, and even more preferably 80% by mass or more.
[0023] Examples of alicyclic tetracarboxylic acids include 1,2,3,4-cyclobutane tetracarboxylic acid, 1,2,3,4-cyclopentane tetracarboxylic acid, 1,2,3,4-cyclohexane tetracarboxylic acid, 1,2,4,5-cyclohexane tetracarboxylic acid, 3,3',4,4'-bicyclohexyl tetracarboxylic acid, bicyclo[2,2,1]heptane-2,3,5,6-tetracarboxylic acid, bicyclo[2,2,2]octane-2,3,5,6-tetracarboxylic acid, and bicyclo[2,2,2]oct-7-ene-2,3,5,6-tetracarboxylic acid. carboxylic acid, tetrahydroanthracene-2,3,6,7-tetracarboxylic acid, tetradecahydro-1,4:5,8:9,10-trimethanoanthracene-2,3,6,7-tetracarboxylic acid, decahydronaphthalene-2,3,6,7-tetracarboxylic acid, decahydro-1,4:5,8-dimethanonaphthalene-2,3,6,7-tetracarboxylic acid, decahydro-1,4-ethano-5,8-methanonaphthalene-2,3,6,7-tetracarboxylic acid, norbornane-2-spiro-α-cyclopentanone-α'-spiro-2''-norbornane -5,5'',6,6''-tetracarboxylic acid (also known as "norbornane-2-spiro-2'-cyclopentanone-5'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic acid"), methylnorbornane-2-spiro-α-cyclopentanone-α'-spiro-2''-(methylnorbornane)-5,5'',6,6''-tetracarboxylic acid, norbornane-2-spiro-α-cyclohexanone-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic acid (also known as "norbornane-2-spiro pyro-2'-cyclohexanone-6'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic acid), methylnorbornane-2-spiro-α-cyclohexanone-α'-spiro-2''-(methylnorbornane)-5,5'',6,6''-tetracarboxylic acid, norbornane-2-spiro-α-cyclopropanone-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic acid, norbornane-2-spiro-α-cyclobutanone-α'-spiro-2''-norbornane-5,5'',6,6''-Tetracarboxylic acid, norbornane-2-spiro-α-cycloheptanone-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic acid, norbornane-2-spiro-α-cyclooctanone-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic acid, norbornane-2-spiro-α-cyclononanone-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic acid, norbornane-2-spiro-α-cyclodecanone-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic acid, norbornane-2-spiro-α-cycloundecanone-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic acid, norbornane-2-spiro-α-cyclododecanone-α'-spiro-2''-norbornane-5,5'' ,6,6''-tetracarboxylic acid, norbornane-2-spiro-α-cyclotridecanone-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic acid, norbornane-2-spiro-α-cyclotetradecanone-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic acid, norbornane-2-spiro-α-cyclopentadecanone-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic acid, norbornane-2-spiro-α-(methylcyclopentanone)-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic acid, and norbornane-2-spiro-α-(methylcyclohexanone)-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic acid, and the like tetracarboxylic acids and their acid anhydrides. Among these, dianhydrides having two acid anhydride structures are preferred, and in particular, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclohexanetetracarboxylic dianhydride, and 1,2,4,5-cyclohexanetetracarboxylic dianhydride are preferred, and 1,2,3,4-cyclobutanetetracarboxylic dianhydride and 1,2,4,5-cyclohexanetetracarboxylic dianhydride are more preferred, and 1,2,3,4-Cyclobutanetetracarboxylic dianhydride is more preferred. These may be used alone or in combination of two or more. When transparency is important, the alicyclic tetracarboxylic acids preferably account for 50% by mass or more of the total tetracarboxylic acids, more preferably 60% by mass or more, even more preferably 70% by mass or more, and even more preferably 80% by mass or more.
[0024] Examples of tricarboxylic acids include aromatic tricarboxylic acids such as trimellitic acid, 1,2,5-naphthalene tricarboxylic acid, diphenyl ether-3,3',4'-tricarboxylic acid, and diphenyl sulfone-3,3',4'-tricarboxylic acid, or hydrogenated products of the aromatic tricarboxylic acids such as hexahydrotrimellitic acid, alkylene glycol bistrimellitates such as ethylene glycol bistrimellitate, propylene glycol bistrimellitate, 1,4-butanediol bistrimellitate, and polyethylene glycol bistrimellitate, and monoanhydrides and esterified products thereof. Among these, monoanhydrides having one acid anhydride structure are preferred, and trimellitic anhydride and hexahydrotrimellitic anhydride are particularly preferred. These may be used alone or in combination.
[0025] Examples of dicarboxylic acids include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, orthophthalic acid, naphthalenedicarboxylic acid, and 4,4'-oxydibenzenecarboxylic acid, or hydrogenated products of the aromatic dicarboxylic acids such as 1,6-cyclohexanedicarboxylic acid, oxalic acid, succinic acid, glutaric acid, adipic acid, heptanedioic acid, octanedioic acid, azelaic acid, sebacic acid, undecadioic acid, dodecanedioic acid, 2-methylsuccinic acid, and acid chlorides or esters thereof. Among these, aromatic dicarboxylic acids and hydrogenated products thereof are preferred, and terephthalic acid, 1,6-cyclohexanedicarboxylic acid, and 4,4'-oxydibenzenecarboxylic acid are particularly preferred. The dicarboxylic acids may be used alone or in combination.
[0026] The diamines or isocyanates for obtaining the colorless and highly transparent polyimide of the present invention are not particularly limited, and aromatic diamines, aliphatic diamines, alicyclic diamines, aromatic diisocyanates, aliphatic diisocyanates, alicyclic diisocyanates, etc., which are usually used in polyimide synthesis, polyamideimide synthesis, and polyamide synthesis, can be used. From the viewpoint of heat resistance, aromatic diamines are preferred, and from the viewpoint of transparency, alicyclic diamines are preferred. In addition, when aromatic diamines having a benzoxazole structure are used, it is possible to develop high elastic modulus, low heat shrinkage, and low linear expansion coefficient as well as high heat resistance. The diamines and isocyanates may be used alone or in combination of two or more kinds.
[0027] Examples of aromatic diamines include 2,2'-dimethyl-4,4'-diaminobiphenyl, 1,4-bis[2-(4-aminophenyl)-2-propyl]benzene, 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene, 2,2'-ditrifluoromethyl-4,4'-diaminobiphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]sulfide, bis [4-(3-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, m-phenylenediamine, o-phenylenediamine, p-phenylenediamine, m-aminobenzylamine, p-aminobenzylamine, 4-amino-N-(4-aminophenyl)benzamide, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether ether, 2,2'-trifluoromethyl-4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 3,4'-diaminobenzophenone, 4,4'-diaminobenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-Diaminodiphenylmethane, 4,4'-Diaminodiphenylmethane, Bis[4-(4-aminophenoxy)phenyl]methane, 1,1-Bis[4-(4-aminophenoxy)phenyl]ethane, 1,2-Bis[4-(4-aminophenoxy)phenyl]ethane, 1,1-Bis[4-(4-aminophenoxy)phenyl]propane, 1,2-Bis[4-(4-aminophenoxy)phenyl]propane, 1,3-Bis[4-(4-aminophenoxy)phenyl]propane, 2,2-Bis[4-(4-aminophenoxy)phenyl]propane, 1,1-bis[4-(4-aminophenoxy)phenyl]butane, 1,3-bis[4-(4-aminophenoxy)phenyl]butane, 1,4-bis[4-(4-aminophenoxy)phenyl]butane, 2,2-bis[4-(4-aminophenoxy)phenyl]butane, 2,3-bis[4-(4-aminophenoxy)phenyl]butane, 2-[4-(4-aminophenoxy)phenyl]-2-[4-(4-aminophenoxy)-3-methylphenyl]propane, 2,2-bis[4-(4-aminophenoxy)-3-methylphenyl]propane, 2-[4-(4-aminophenoxy)phenyl]-2-[4-(4-aminophenoxy)-3,5-dimethylphenyl]propane, 2,2-bis[4-(4-aminophenoxy)-3,5-dimethylphenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 1,4-bis(3-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl , bis[4-(4-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfoxide, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, 1,3-bis[4-(4-aminophenoxy)benzoyl]benzene, 1,3-bis[4-(3-aminophenoxy)benzoyl]benzene, 1,4-bis[4-(3-aminophenoxy)benzoyl]benzene, 1,1-bis[4-(3-aminophenoxy)phenyl]propane, 1,3-bis[4-(3-aminophenoxy)phenyl]propane, 3,4'-diaminodiphenyl sulfide, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, bis[4-(3-aminophenoxy)phenyl]methane, 1,1-bis[4-(3-aminophenoxy)phenyl]ethane, 1,2-bis[4-(3-aminophenoxy)phenyl]ethane, bis[4-(3-aminophenoxy)phenyl]sulfoxide, 4,4'-bis[3-(4-aminophenoxy)benzoyl]diphenyl ether, 4,4'-bis[3-(3-aminophenoxy)benzoyl]diphenyl ether, 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]benzophenone, 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]diphenyl sulfone, bis[4-{4-(4-aminophenoxy)pheno 1,4-bis[4-(4-aminophenoxy)phenoxy-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-aminophenoxy)phenoxy-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-trifluoromethylphenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-fluorophenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-methylphenoxy)-α,α-dimethylbenzyl]benzene , 1,3-bis[4-(4-amino-6-cyanophenoxy)-α,α-dimethylbenzyl]benzene, 3,3'-diamino-4,4'-diphenoxybenzophenone, 4,4'-diamino-5,5'-diphenoxybenzophenone, 3,4'-diamino-4,5'-diphenoxybenzophenone, 3,3'-diamino-4-phenoxybenzophenone, 4,4'-diamino-5-phenoxybenzophenone, 3,4'-diamino-4-phenoxybenzophenone, 3,4'-diamino-5'-phenoxybenzophenone, 3,3'-diamino-4, 4'-Diamino-5,5'-diamino-diamino-4 ...Examples of the aromatic diamine include 3-bis(4-amino-5-phenoxybenzoyl)benzene, 1,4-bis(4-amino-5-phenoxybenzoyl)benzene, 1,3-bis(3-amino-4-biphenoxybenzoyl)benzene, 1,4-bis(3-amino-4-biphenoxybenzoyl)benzene, 1,3-bis(4-amino-5-biphenoxybenzoyl)benzene, 1,4-bis(4-amino-5-biphenoxybenzoyl)benzene, 2,6-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]benzonitrile, and aromatic diamines in which some or all of the hydrogen atoms on the aromatic ring of the above-mentioned aromatic diamines are substituted with halogen atoms, alkyl groups or alkoxy groups having 1 to 3 carbon atoms, cyano groups, or halogenated alkyl groups or alkoxy groups having 1 to 3 carbon atoms in which some or all of the hydrogen atoms of the alkyl groups or alkoxy groups are substituted with halogen atoms. The aromatic diamines having a benzoxazole structure are not particularly limited, and examples thereof include 5-amino-2-(p-aminophenyl)benzoxazole, 6-amino-2-(p-aminophenyl)benzoxazole, 5-amino-2-(m-aminophenyl)benzoxazole, 6-amino-2-(m-aminophenyl)benzoxazole, 2,2'-p-phenylenebis(5-aminobenzoxazole), 2,2'-p-phenylenebis(6-aminobenzoxazole), 1-(5-aminobenzoxazolo)-4-(6-aminobenzoxazolo)benzene, 2,6-(4,4'- 2,6-(4,4'-diaminodiphenyl)benzo[1,2-d:4,5-d']bisoxazole, 2,6-(3,4'-diaminodiphenyl)benzo[1,2-d:5,4-d']bisoxazole, 2,6-(3,4'-diaminodiphenyl)benzo[1,2-d:4,5-d']bisoxazole, 2,6-(3,4'-diaminodiphenyl)benzo[1,2-d:4,5-d']bisoxazole, 2,6-(3,3'-diaminodiphenyl)benzo[1,2-d:5,4-d']bisoxazole, 2,6-(3,3'-diaminodiphenyl)benzo[1,2-d:4,5-d']bisoxazole, etc. Among these, 2,2'-ditrifluoromethyl-4,4'-Diaminobiphenyl, 4-amino-N-(4-aminophenyl)benzamide, 4,4'-diaminodiphenyl sulfone, and 3,3'-diaminobenzophenone are preferred. The aromatic diamines may be used alone or in combination.
[0028] Examples of alicyclic diamines include 1,4-diaminocyclohexane, 1,4-diamino-2-methylcyclohexane, 1,4-diamino-2-ethylcyclohexane, 1,4-diamino-2-n-propylcyclohexane, 1,4-diamino-2-isopropylcyclohexane, 1,4-diamino-2-n-butylcyclohexane, 1,4-diamino-2-isobutylcyclohexane, 1,4-diamino-2-sec-butylcyclohexane, 1,4-diamino-2-tert-butylcyclohexane, and 4,4'-methylenebis(2,6-dimethylcyclohexylamine). Among these, 1,4-diaminocyclohexane and 1,4-diamino-2-methylcyclohexane are particularly preferred, and 1,4-diaminocyclohexane is more preferred. The alicyclic diamines may be used alone or in combination.
[0029] Examples of diisocyanates include diphenylmethane-2,4'-diisocyanate, 3,2'- or 3,3'- or 4,2'- or 4,3'- or 5,2'- or 5,3'- or 6,2'- or 6,3'-dimethyldiphenylmethane-2,4'-diisocyanate, 3,2'- or 3,3'- or 4,2'- or 4,3'- or 5,2'- or 5,3'- or 6,2'- or 6,3'-diethyl Diphenylmethane-2,4'-diisocyanate, 3,2'- or 3,3'- or 4,2'- or 4,3'- or 5,2'- or 5,3'- or 6,2'- or 6,3'-dimethoxydiphenylmethane-2,4'-diisocyanate, diphenylmethane-4,4'-diisocyanate, diphenylmethane-3,3'-diisocyanate, diphenylmethane-3,4'-diisocyanate, diphenylether-4,4' -Diisocyanates, benzophenone-4,4'-diisocyanate, diphenylsulfone-4,4'-diisocyanate, tolylene-2,4-diisocyanate, tolylene-2,6-diisocyanate, m-xylylene diisocyanate, p-xylylene diisocyanate, naphthalene-2,6-diisocyanate, 4,4'-(2,2-bis(4-phenoxyphenyl)propane)diisocyanate, 3,3'- or 2,2'-dimethylbiphenyl-4,4'-diisocyanate, 3,3'- or 2,2'-di Examples of the diisocyanates include aromatic diisocyanates such as ethylbiphenyl-4,4'-diisocyanate, 3,3'-dimethoxybiphenyl-4,4'-diisocyanate, and 3,3'-diethoxybiphenyl-4,4'-diisocyanate, and diisocyanates obtained by hydrogenating any of these diisocyanates (for example, isophorone diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and hexamethylene diisocyanate).Among these, diphenylmethane-4,4'-diisocyanate, tolylene-2,4-diisocyanate, tolylene-2,6-diisocyanate, 3,3'-dimethylbiphenyl-4,4'-diisocyanate, naphthalene-2,6-diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and 1,4-cyclohexane diisocyanate are preferred from the viewpoints of low moisture absorption, dimensional stability, cost, and polymerizability. The diisocyanates may be used alone or in combination.
[0030] The yellowness index of the polyimide film in the present invention is preferably 10 or less, more preferably 7 or less, even more preferably 5 or less, and even more preferably 3 or less. There is no particular lower limit to the yellowness index of the polyimide film, but for use as a flexible electronic device, it is preferably 0.1 or more, more preferably 0.2 or more, and even more preferably 0.3 or more.
[0031] The polyimide film of the present invention has a light transmittance at a wavelength of 400 nm of preferably 70% or more, more preferably 72% or more, even more preferably 75% or more, and even more preferably 80% or more. There is no particular upper limit to the light transmittance at a wavelength of 400 nm of the polyimide film, but for use as a flexible electronic device, it is preferably 99% or less, more preferably 98% or less, and even more preferably 97% or less.
[0032] The total light transmittance of the polyimide film in the present invention is preferably 85% or more, more preferably 86% or more, even more preferably 87% or more, and even more preferably 88% or more. There is no particular upper limit to the total light transmittance of the polyimide film, but in order to use the polyimide film as a flexible electronic device, it is preferably 99% or less, more preferably 98% or less, and even more preferably 97% or less.
[0033] The haze of the polyimide film in the present invention is preferably 1.0 or less, more preferably 0.8 or less, even more preferably 0.5 or less, and even more preferably 0.3 or less. The upper limit of the light transmittance of the polyimide film at a wavelength of 400 nm is not particularly limited, but for use as a flexible electronic device, it is preferably 99% or less, more preferably 98% or less, and even more preferably 97% or less.
[0034] The thickness of the polyimide film in the present invention is preferably 3 μm or more, more preferably 11 μm or more, even more preferably 24 μm or more, and even more preferably 45 μm or more. There is no particular upper limit to the thickness of the polyimide film, but in order to use it as a flexible electronic device, it is preferably 250 μm or less, more preferably 150 μm or less, and even more preferably 90 μm or less.
[0035] The average CTE of the polyimide film in the present invention between 30°C and 300°C is preferably -5 ppm / °C to +55 ppm / °C, more preferably -5 ppm / °C to +45 ppm / °C, even more preferably -5 ppm / °C to +35 ppm / °C, even more preferably -5 ppm / °C to +20 ppm / °C, and even more preferably 1 ppm / °C to +10 ppm / °C. When the CTE is in the above range, the difference in linear expansion coefficient with a general support (inorganic substrate) can be kept small, and peeling between the polyimide film and the inorganic substrate can be prevented even when the polyimide film is subjected to a process in which heat is applied. Here, CTE is a factor that indicates reversible expansion and contraction with respect to temperature. The CTE of the polyimide film refers to the average value of the CTE in the machine direction (MD) and the CTE in the width direction (TD) of the polyimide film. The CTE of the polyimide film is measured by the method described in the Examples. The colorless and highly transparent polyimide film of the present invention, which shows a linear expansion coefficient, can be realized by performing stretching during the film formation process of the polyimide film. The stretching operation can be realized by applying a polyimide solution to a support for preparing a polyimide film, drying the polyimide film containing 1 to 50% by weight of a solvent, and then stretching the polyimide film containing 1 to 50% by weight of a solvent at a high temperature on the support for preparing a polyimide film or in a state where the polyimide film is peeled off from the support, to 1.5 to 4.0 times in the MD direction and 1.4 to 3.0 times in the TD direction during the process of drying. In this case, an unstretched thermoplastic polymer film is used as the support for preparing a polyimide film, and the thermoplastic polymer film and the polyimide film are stretched simultaneously, and then the stretched polyimide film is peeled off from the thermoplastic polymer film, thereby preventing scratches on the polyimide film, especially during stretching in the MD direction, and a higher quality colorless and highly transparent polyimide film can be obtained.
[0036] The heat shrinkage of the polyimide film of the present invention is preferably ±0.9%, and more preferably ±0.6%, between 30° C. and 500° C. The heat shrinkage is a factor that indicates irreversible expansion and contraction with respect to temperature.
[0037] The tensile breaking strength of the polyimide film of the present invention is preferably 60 MPa or more, more preferably 120 MPa or more, and even more preferably 240 MPa or more. The upper limit of the tensile breaking strength is not particularly limited, but is practically less than about 1000 MPa. If the tensile breaking strength is 60 MPa or more, it is possible to prevent the polyimide film from breaking when peeling it off from an inorganic substrate. The tensile breaking strength of the polyimide film refers to the average value of the tensile breaking strength in the machine direction (MD direction) and the tensile breaking strength in the width direction (TD direction) of the polyimide film. The tensile breaking strength of the polyimide film is measured by the method described in the Examples.
[0038] The tensile elongation at break of the polyimide film of the present invention is preferably 1% or more, more preferably 5% or more, and even more preferably 10% or more. When the tensile elongation at break is 1% or more, the film has excellent handleability. The tensile elongation at break of the polyimide film refers to the average value of the tensile elongation at break in the machine direction (MD) and the tensile elongation at break in the width direction (TD) of the polyimide film. The tensile elongation at break of the polyimide film is measured by the method described in the Examples.
[0039] The tensile modulus of the polyimide film of the present invention is preferably 3 GPa or more, more preferably 4 GPa or more, and even more preferably 5 GPa or more. When the tensile modulus is 3 GPa or more, the polyimide film is less elongated and deformed when peeled off from an inorganic substrate, and is excellent in handleability. The tensile modulus is preferably 20 GPa or less, more preferably 12 GPa or less, and even more preferably 10 GPa or less. When the tensile modulus is 20 GPa or less, the polyimide film can be used as a flexible film. The tensile modulus of the polyimide film refers to the average value of the tensile modulus of the polyimide film in the machine direction (MD direction) and the tensile modulus of the polyimide film in the width direction (TD direction). The tensile modulus of the polyimide film is measured by the method described in the Examples.
[0040] The thickness unevenness of the polyimide film of the present invention is preferably 20% or less, more preferably 12% or less, even more preferably 7% or less, and particularly preferably 4% or less. If the thickness unevenness exceeds 20%, it tends to be difficult to apply to narrow parts. The thickness unevenness of the film can be calculated, for example, by measuring the film thickness at about 10 randomly selected positions on the film to be measured using a contact type film thickness meter, and then calculating the thickness unevenness based on the following formula. Film thickness unevenness (%) = 100 x (maximum film thickness - minimum film thickness) ÷ average film thickness
[0041] The polyimide film of the present invention is preferably obtained in the form of a long polyimide film wound up to a width of 300 mm or more and a length of 10 m or more during production, and more preferably in the form of a roll-shaped polyimide film wound up on a winding core. When the polyimide film is wound up in a roll, it is easy to transport it in the form of a roll-shaped polyimide film.
[0042] In the polyimide film of the present invention, in order to ensure the handling property and productivity, it is preferable to add or contain about 0.03 to 3 mass % of a lubricant (particles) having a particle diameter of about 10 to 1000 nm in the polyimide film, thereby imparting fine irregularities to the surface of the polyimide film and ensuring the slipperiness.
[0043] The inorganic substrate of the present invention may be any plate-like substrate that can be used as a substrate made of an inorganic material, and examples thereof include those that are mainly made of a glass plate, a ceramic plate, a semiconductor wafer, a metal, etc., and composites of these glass plates, ceramic plates, semiconductor wafers, and metals, such as laminates thereof, composites in which these are dispersed, and composites in which fibers of these are contained. In the present invention, an inorganic substrate that does not contain nitrogen as a constituent element is preferably used.
[0044] The glass plate includes quartz glass, high silica glass (96% silica), soda-lime glass, lead glass, aluminoborosilicate glass, borosilicate glass (Pyrex (registered trademark)), borosilicate glass (alkali-free), borosilicate glass (microsheet), aluminosilicate glass, etc. Among these, those with a linear expansion coefficient of 5 ppm / K or less are preferable, and among commercially available products, glass for liquid crystal displays such as "Corning (registered trademark) 7059", "Corning (registered trademark) 1737", and "EAGLE" manufactured by Corning Incorporated, "AN100" manufactured by Asahi Glass Co., Ltd., "OA10" and "OA11" manufactured by Nippon Electric Glass Co., Ltd., and "AF32" manufactured by SCHOTT are preferable.
[0045] The semiconductor wafer is not particularly limited, but examples thereof include silicon wafers, germanium, silicon-germanium, gallium-arsenide, aluminum-gallium-indium, nitrogen-phosphorus-arsenic-antimony, SiC, InP (indium phosphide), InGaAs, GaInNAs, LT, LN, ZnO (zinc oxide), CdTe (cadmium tellurium), ZnSe (zinc selenide), etc. Among these, the wafers preferably used are silicon wafers, and particularly preferably mirror-polished silicon wafers having a size of 8 inches or more.
[0046] The metals include single element metals such as W, Mo, Pt, Fe, Ni, and Au, and alloys such as Inconel, Monel, Nimonic, carbon copper, Fe-Ni-based Invar alloy, and Super Invar alloy. Also included are multilayer metal plates formed by adding other metal layers and ceramic layers to these metals. In this case, Cu, Al, etc. are used for the main metal layer if the overall coefficient of linear expansion (CTE) with the additional layer is low. The metals used for the additional metal layer are not limited as long as they have properties such as strengthening adhesion to the polyimide film, not diffusing, and good chemical resistance and heat resistance, but suitable examples include Cr, Ni, TiN, and Mo-containing Cu.
[0047] The planar portion of the inorganic substrate is preferably sufficiently flat. Specifically, the PV value of the surface roughness is 50 nm or less, more preferably 20 nm or less, and further preferably 5 nm or less. If it is rougher than this, the adhesive strength between the polyimide film layer and the inorganic substrate may be insufficient.
[0048] The thickness of the inorganic substrate is not particularly limited, but from the viewpoint of handling, the thickness is preferably 10 mm or less, more preferably 3 mm or less, and even more preferably 1.3 mm or less. The lower limit of the thickness is not particularly limited, but is preferably 0.05 mm or more, more preferably 0.3 mm or more, and even more preferably 0.5 mm or more.
[0049] The silane coupling agent of the present invention is physically or chemically present between the inorganic substrate and the metal-containing layer, and has the effect of bonding the inorganic substrate and the polyimide film. Specific preferred examples of the silane coupling agent include N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride, aminophenyltrimethoxysilane, aminophenethyltrimethoxysilane, and aminophenylaminomethylphenethyltrimethoxysilane.
[0050] Among the above-mentioned silane coupling agents, silane coupling agents having one silicon atom in one molecule are particularly preferred, such as N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, aminophenyltrimethoxysilane, aminophenethyltrimethoxysilane, aminophenylaminomethylphenethyltrimethoxysilane, etc. When particularly high heat resistance is required in the process, it is desirable to use an aromatic group to connect between Si and amino group. In addition to the above, 11-amino-1-undecenethiol can also be used as the coupling agent.
[0051] An example of the silane coupling agent is a polyamine compound.
[0052] The silane coupling agent layer can be formed by applying a silane coupling agent solution to the inorganic substrate, by vapor deposition, etc. The silane coupling agent layer may be formed on the surface of the heat-resistant polymer.
[0053] As a method for applying the silane coupling agent solution, a solution obtained by diluting the silane coupling agent with a solvent such as alcohol can be appropriately used by a conventionally known solution application means such as spin coating, curtain coating, dip coating, slit die coating, gravure coating, bar coating, comma coating, applicator method, screen printing, spray coating, etc.
[0054] The silane coupling agent layer can also be formed by a vapor deposition method, specifically, by exposing the inorganic substrate to the vapor of the silane coupling agent, i.e., the silane coupling agent in a substantially gaseous state. The vapor of the silane coupling agent can be obtained by heating the silane coupling agent in a liquid state to a temperature of 40°C to the boiling point of the silane coupling agent. The boiling point of the silane coupling agent varies depending on the chemical structure, but is generally in the range of 100 to 250°C. However, heating to 200°C or higher is not preferred because it may cause a side reaction on the organic group side of the silane coupling agent. The environment in which the silane coupling agent is heated may be under pressure, normal pressure, or reduced pressure, but in order to promote the vaporization of the silane coupling agent, normal pressure or reduced pressure is preferable. Since most silane coupling agents are flammable liquids, it is preferable to carry out the vaporization process in a sealed container, preferably after replacing the inside of the container with an inert gas. The time for exposing the inorganic substrate to the silane coupling agent is not particularly limited, but is preferably within 20 hours, more preferably within 60 minutes, even more preferably within 15 minutes, and most preferably within 1 minute. The temperature of the inorganic substrate during exposure to the silane coupling agent is preferably controlled to an appropriate temperature between -50°C and 200°C depending on the type of silane coupling agent and the desired thickness of the silane coupling agent layer.
[0055] The thickness of the silane coupling agent layer is extremely thin compared to inorganic substrates, polyimide films, etc., and is negligible from the viewpoint of mechanical design, and in principle, a thickness of the order of a monolayer is sufficient. Generally, it is less than 20 nm, preferably 15 nm or less, more preferably 10 nm or less in practical use, more preferably 7 nm or less, and even more preferably 5 nm or less. However, when the calculated thickness is in the range of 5 nm or less, the silane coupling agent layer may exist in the form of clusters rather than as a uniform coating film. The thickness of the silane coupling agent layer can be calculated by the ellipsometry method or the concentration of the silane coupling agent solution during coating and the amount of coating.
[0056] The laminate of the present invention is [A method] (1) applying a silane coupling agent to at least one surface of an inorganic substrate; (2) wetting either or both of the silane coupling agent-coated surface of the inorganic substrate and the adhesive surface of the polyimide film with an aqueous medium; (3) a step of laminating a polyimide film on the silane coupling agent-coated surface of the inorganic substrate; (4) a step of pressing the silane coupling agent-coated surface of the inorganic substrate and the adhesive surface of the polyimide film together while extruding the aqueous medium from between them; The above steps are preferably carried out in this order. In addition, in the present invention [B method] (1) applying a silane coupling agent to at least one surface of a heat-resistant polyimide film; (2) Wetting either or both of the adhesive surface of the inorganic substrate and the silane coupling agent-coated surface of the polyimide film with an aqueous medium; (3) a step of superposing a silane coupling agent-coated surface of a heat-resistant polyimide film on the inorganic substrate; (4) a step of pressing the adhesive surface of the inorganic substrate and the silane coupling agent-coated surface of the polyimide film together while extruding the aqueous medium from between them; The above steps are preferably carried out in this order.
[0057] The aqueous medium is a general term for liquids that are not reactive at room temperature, and so-called solvents can be used. The aqueous medium preferably used in the present invention is water, a monohydric alcohol, a dihydric alcohol, a trihydric alcohol that is liquid at room temperature, or a mixture containing two or more of these components.
[0058] As a method for wetting the adhesive surface of the substrate or film with the aqueous medium, existing methods can be applied, such as dropping with a dropper or dispenser, discharging from a valve, spraying in mist form from a spray nozzle, etc. Also, immersing the substrate or film in the aqueous medium is an effective means for wetting. When a liquid containing water or alcohol is used as the aqueous medium, it also contributes to accelerating the reaction of the silane coupling agent.
[0059] The method of laminating the substrate and the film can be a pressing method, a roll lamination method, or the like. For example, pressure can be applied in a planar or linear manner by pressing, laminating, or roll laminating under atmospheric pressure or in a vacuum. The process can also be accelerated by heating during pressure application. In the present invention, pressing or roll lamination under atmospheric pressure is preferred, and a method using a roll (roll lamination, etc.) is particularly preferred because the aqueous medium at the adhesive interface can be sequentially pushed out from the adhesive surface while laminating.
[0060] The pressure during the pressurized heat treatment is preferably 0.1 MPa to 20 MPa, and more preferably 0.2 MPa to 3 MPa. If it is 20 MPa or less, damage to the inorganic substrate can be suppressed. If it is 0.1 MPa or more, the occurrence of non-adhered areas and insufficient adhesion can be prevented. The temperature during the pressurized heat treatment is preferably 80°C to 400°C, and more preferably 100°C to 200°C. If the temperature is too high, the polyimide film may be damaged, and if the temperature is too low, the adhesion tends to be weakened. Although the pressurized heat treatment can be performed in an atmospheric pressure environment as described above, it may be possible to obtain a more uniform adhesive strength by performing the treatment under a vacuum. The degree of vacuum achieved by a normal oil rotary pump is sufficient, and a vacuum of about 10 Torr or less is sufficient. As for equipment that can be used for pressure and heat treatment, for example, the "11FD" manufactured by Imoto Manufacturing Co., Ltd. can be used for pressing in a vacuum, and for vacuum lamination using a roll-type film laminator in a vacuum or a film laminator that applies pressure to the entire surface of the glass at once using a thin rubber film after creating a vacuum, for example, the "MVLP" manufactured by Meiki Manufacturing Co., Ltd. can be used.
[0061] The pressurized and heated treatment can be carried out separately into a pressurizing process and a heating process. In this case, the polyimide film and the inorganic substrate are first pressurized (preferably about 0.2 to 50 MPa) at a relatively low temperature (for example, less than 120°C, more preferably 80 to 110°C) to ensure adhesion between them, and then heated under pressure (preferably 20 MPa or less, 0.2 MPa or more) or at normal pressure at a relatively high temperature (for example, 80°C or more, more preferably 100 to 250°C, even more preferably 120 to 220°C), whereby a chemical reaction at the adhesive interface is promoted to laminate the polyimide film and the inorganic substrate.
[0062] In this manner, a laminate in which the inorganic substrate and the polyimide film are bonded together can be obtained. However, the method for producing the laminate according to the present invention is not limited to this example. As another example, pure water may be dropped on the polyimide film side, so that the silane coupling agent layer comes into contact with water when laminated to form a desired silane coupling agent layer, and then the inorganic substrate may be bonded almost at the same time. In addition, the inorganic substrates may be bonded together by dropping pure water onto both the polyimide film side and the inorganic substrate to promote the reaction of the silane coupling agent and achieve a desired bonded state.
[0063] Thus, in the present invention, a laminate can be obtained in which the 90-degree initial adhesive strength between the polyimide film and the inorganic substrate is 0.06 N / cm or more and 0.25 N / cm or less, the blister defect density is one or less per 500 mm x 500 mm, and preferably the area is 0.8 square meters or more and the length of at least one side is 1 m or more.
[0064] In the laminate, the 90-degree initial adhesive strength between the polyimide film and the inorganic substrate must be 0.06 N / cm or more, more preferably 0.09 N / cm or more, and even more preferably 0.1 N / cm or more. The 90-degree initial adhesive strength must be 0.25 N / cm or less, and more preferably 0.2 N / cm or less. If the 90-degree initial adhesive strength is 0.05 N / cm or more, the polyimide film can be prevented from peeling off from the inorganic substrate before or during device formation. If the 90-degree initial adhesive strength is 0.25 N / cm or less, the inorganic substrate and the polyimide film can be easily peeled off after device formation. In other words, if the 90-degree initial adhesive strength is 0.25 N / cm or less, even if the adhesive strength between the inorganic substrate and the polyimide film increases slightly during device formation, the two can be easily peeled off. In this specification, the 90 degree initial adhesive strength refers to the 90 degree adhesive strength between the inorganic substrate and the polyimide film after the laminate is heat-treated at 200° C. for 1 hour in an air atmosphere.
[0065] The conditions for measuring the 90 degree initial adhesive strength are as follows. The polyimide film is peeled off at a 90 degree angle from the inorganic substrate. The measurement is carried out five times and the average value is taken as the measured value. Measurement temperature: Room temperature (25℃) Peel speed: 100mm / min atmosphere; atmosphere Measurement sample width: 2.5cm More specifically, according to the method described in the Examples.
[0066] In the present invention, a functional element is formed on the surface of the laminate obtained by the above-mentioned method A or B opposite to the adhesive surface of the polyimide film, and after formation of the functional element, the polyimide film is peeled off from the substrate, thereby making it possible to produce a flexible electronic device.
[0067] In this specification, the term "electronic device" refers to wiring boards having a single-sided, double-sided, or multi-layer structure that carry electrical wiring, electronic circuits including active elements such as transistors and diodes, and passive devices such as resistors, capacitors, and inductors, as well as sensor elements that sense pressure, temperature, light, humidity, etc., biosensor elements, light-emitting elements, image display elements such as liquid crystal displays, electrophoretic displays, and self-luminous displays, wireless and wired communication elements, computing elements, memory elements, MEMS elements, solar cells, thin film transistors, etc.
[0068] In the method for producing a flexible electronic device in this specification, after an electronic device is formed on the polyimide film surface of the laminate produced by the above-mentioned method, the polyimide film is peeled off from the inorganic substrate.
[0069] The method of peeling the polyimide film on which the electronic device is formed from the inorganic substrate is not particularly limited, but may be, for example, a method of rolling up from the edge with tweezers, a method of making a cut in the polyimide film, attaching an adhesive tape to one side of the cut, and then rolling up from the tape, or a method of vacuum-adsorbing one side of the cut in the polyimide film and then rolling up from that part. Note that, if a small curvature is generated at the cut in the polyimide film during peeling, stress is applied to the device at that part, which may destroy the device, so it is desirable to peel it off with as large a curvature as possible. For example, it is desirable to roll up the film while winding it around a roll with a large curvature, or to roll it up using a machine configured so that a roll with a large curvature is located at the peeling part. The method of making the cuts in the polyimide film includes, but is not limited to, a method of cutting the polyimide film with a cutting tool such as a blade, a method of cutting the polyimide film by scanning a laser and a laminate relatively, a method of cutting the polyimide film by scanning a water jet and a laminate relatively, a method of cutting the polyimide film while cutting a little into the glass layer with a semiconductor chip dicing device, etc. For example, when adopting the above-mentioned method, a method of superimposing ultrasonic waves on the cutting tool or adding a reciprocating motion or an up-and-down motion to improve cutting performance can be appropriately adopted. In addition, a method of attaching another reinforcing substrate to the portion to be peeled off and peeling off the reinforcing substrate together is also useful. When the flexible electronic device to be peeled off is a backplane of a display device, it is also possible to attach a frontplane of the display device to the inorganic substrate in advance, integrate the substrate on the inorganic substrate, and then peel off the two at the same time to obtain a flexible display device. EXAMPLES
[0070] The present invention will be described in detail below using examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention.
[0071] In the examples and comparative examples, the respective measured values were measured by the following methods unless otherwise specified.
[0072] <Reduced viscosity of polymer> The polymer was dissolved in N-methyl-2-pyrrolidone (or N,N-dimethylacetamide) so that the polymer concentration was 0.2 g / dl, and the solution was measured at 30°C using an Ubbelohde type viscosity tube. (When the solvent used to prepare the polyamic acid solution was N,N-dimethylacetamide, the polymer was dissolved in N,N-dimethylacetamide and the measurement was performed.)
[0073] <Area surface roughness, maximum protrusion height, and peak density of support for preparing polyimide film> The area surface roughness (Sa), maximum peak height (Sp), and peak density (Spd) of the support for preparing the polyimide film were measured in accordance with ISO 25178-2:2012.
[0074] <Polyimide film thickness> The measurement was carried out using a micrometer (Militron 1245D, manufactured by Feinruf Co., Ltd.).
[0075] <Tensile modulus, tensile strength at break, and tensile elongation at break of polyimide film> Polyimide film was cut into strips of 100 mm x 10 mm in both the machine direction (MD) and the width direction (TD) to prepare test pieces. The test pieces were cut from the center of the width direction. Using a tensile tester (Shimadzu Corporation, Autograph (R), model name AG-5000A), the tensile modulus, tensile breaking strength, and tensile breaking elongation were measured in both the MD and TD directions under the conditions of a temperature of 25°C, a tensile speed of 50 mm / min, and a chuck distance of 40 mm.
[0076] <Coefficient of Linear Expansion (CTE)> The expansion / contraction rate of the polyimide film was measured in the machine direction (MD) and width direction (TD) under the following conditions. The expansion / contraction rate / temperature was measured at intervals of 15°C, such as 30°C to 45°C and 45°C to 60°C. This measurement was continued up to 300°C, and the average value of all the measured values was calculated as the CTE. Equipment name: MAC Science TMA4000S Sample length: 20mm Sample width: 2mm Heating start temperature: 25℃ Heating end temperature: 400℃ Heating rate: 5℃ / min Atmosphere: Argon
[0077] <Measurement of adhesive strength> The adhesive strength of the polyimide film from the laminate obtained in the preparation of the laminate was measured by the 90 degree peeling method as follows. The film is peeled off at a 90 degree angle from the inorganic substrate. Measuring device: Shimadzu Autograph AG-IS Measurement temperature: Room temperature (25℃) Peel speed: 100mm / min atmosphere; atmosphere Measurement sample width: 2.5cm The measurements were taken at five points in total, including the center and each of the four corners of the laminate, and the average value was calculated.
[0078] The measurements were performed after heat-treating the laminate in an air atmosphere at 200°C for 1 hour and after further heat-treating it at 450°C for 1 hour after the heat treatment. The former was the initial adhesive strength and the latter was the adhesive strength after heat treatment.
[0079] <Counting blister defects> In the present invention, blisters with a major axis of 300 μm or more were counted as blisters. Blisters are also called floating defects or air bubble defects, and are areas where the film is not adhered to the substrate and floats up like a bubble. They often occur when a relatively hard foreign object pinches the film and lifts it up like a tent. In the present invention, the laminate is observed under magnification with the focus on the adhesive surface between the inorganic substrate and the polyimide film, and the number of blisters with a major axis of 300 μm or more is counted at least For G2 (370mm x 470mm) size laminates, 4 sheets For G4.5 (730mm x 920mm) size laminates, 2 sheets For G5 (1100mm x 1250mm) size laminates, one sheet The number of particles was counted and converted to the number per square meter.
[0080] <Yellowness Index (YI)> Using a color meter (ZE6000, Nippon Denshoku Industries Co., Ltd.) and a C2 light source, the tristimulus values XYZ of the polyimide film were measured according to ASTM D1925, and the yellowness index (YI) was calculated according to the following formula. The same measurement was performed three times, and the arithmetic average value was used. YI=100×(1.28X-1.06Z) / Y
[0081] <400nm light transmittance> The light transmittance at a wavelength of 400 nm was measured using a spectrophotometer (Hitachi U-2001), and the obtained value was converted to a thickness of 20 μm according to the Beer-Lambert law, and the obtained value was regarded as the 400 nm light transmittance of the polyimide film. The same measurement was performed three times, and the arithmetic average value was used.
[0082] <Total light transmittance (TT)> The total light transmittance (TT) of the polyimide film was measured using a HAZEMETER (NDH5000, manufactured by Nippon Denshoku Co., Ltd.). A D65 lamp was used as the light source. The same measurement was performed three times, and the arithmetic average value was used.
[0083] <Haze value (HAZE)> The haze of the polyimide film was measured using a HAZEMETER (NDH5000, manufactured by Nippon Denshoku Co., Ltd.). A D65 lamp was used as the light source. The same measurement was performed three times, and the arithmetic average value was used.
[0084] [Preparation of polyamic acid solution A] After replacing the atmosphere in a reaction vessel equipped with a nitrogen inlet tube, a thermometer, and a stirring rod with nitrogen, 176.5g (0.900 mol) of 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), 31.0g (0.100mol) of 4,4'-oxydiphthalic acid (ODPA), 160.1g (0.500 mol) of 2,2'-ditrifluoromethyl-4,4'-diaminobiphenyl (TFMB), 113.6g (0.500mol) of 4-amino-N-(4-aminophenyl)benzamide (DABAN), and 2000g of N,N-dimethylacetamide were charged in a nitrogen atmosphere and dissolved in the reaction vessel, and then stirred at room temperature for 24 hours. After that, it was diluted with 1000g of N,N-dimethylacetamide to obtain a polyamic acid solution A with a reduced viscosity of 4.50 dl / g.
[0085] [Preparation of polyimide solution B] After replacing the inside of a reaction vessel equipped with a nitrogen inlet tube, a thermometer, and a stirring rod with nitrogen, 461g of N,N-dimethylacetamide (DMAC) and 64.0g (0.200mol) of 2,2'-ditrifluoromethyl-4,4'-diaminobiphenyl (TFMB) were added to the reaction vessel under a nitrogen atmosphere and stirred to dissolve TFMB in DMAC. Next, while stirring the inside of the reaction vessel, 89.737g (0.202mol) of 4,4'-(2,2-hexafluoroisopropylidene)diphthalic anhydride (6FDA) was added over about 10 minutes under a nitrogen stream, and the polymerization reaction was carried out by continuing stirring for 6 hours while adjusting the temperature to be in the range of 20 to 40°C, and a viscous polyamic acid solution was obtained. Next, the obtained polyamic acid solution was diluted with 410 g of DMAC, and then 25.83 g of isoquinoline was added as an imidization accelerator. The polyamic acid solution was kept at a temperature of 30 to 40°C while being stirred, and 122.5 g (1.20 mol) of acetic anhydride was slowly added dropwise as an imidization agent over a period of about 10 minutes. Thereafter, the liquid temperature was further kept at 30 to 40°C and stirring was continued for 12 hours to carry out a chemical imidization reaction, thereby obtaining a polyimide solution. Next, 1000 g of the obtained polyimide solution containing the imidization agent and the imidization accelerator was transferred to a reaction vessel equipped with a stirrer and agitator, and the temperature was kept at 15 to 25 ° C while stirring at a speed of 120 rpm, and 1500 g of methanol was dropped therein at a rate of 10 g / min. When about 800 g of methanol was added, the polyimide solution became turbid and precipitation of powder-like polyimide was confirmed. The entire amount of methanol, 1500 g, was then added, and the precipitation of polyimide was completed. Next, the contents of the reaction vessel were filtered using a suction filtration device, and further washed and filtered using 1000 g of methanol. Then, 50 g of the filtered polyimide powder was dried at 50 ° C for 24 hours using a dryer equipped with a local exhaust device, and further dried at 260 ° C for 2 hours to remove the remaining volatile components, and a polyimide powder was obtained. The reduced viscosity of the obtained polyimide powder was 5.40 dl / g. Next, 40 g of the obtained polyimide powder was dissolved in 300 g of DMAc to obtain a polyimide solution B.
[0086] [Preparation of polyimide solution C] In a reaction vessel equipped with a nitrogen inlet tube, a Dean-Stark tube, a reflux tube, a thermometer, and a stirrer, 120.5g (0.485mol) of 4,4'-diaminodiphenylsulfone (4,4'-DDS), 51.6g (0.208mol) of 3,3'-diaminodiphenylsulfone (3,3'-DDS), and 500g of gamma-butyrolactone (GBL) were added while introducing nitrogen gas. Then, 217.1g (0.700mol) of 4,4'-oxydiphthalic acid non-dihydrate (ODPA), 223g of GBL, and 260g of toluene were added at room temperature, and the internal temperature was raised to 160°C and heated to reflux at 160°C for 1 hour to perform imidization. After completion of imidization, the temperature was raised to 180°C, and the reaction was continued while drawing out toluene. After reaction for 12 hours, the oil bath was removed and the mixture was returned to room temperature, and GBL was added so that the solid content became 20% by mass, to obtain a polyimide solution C having a reduced viscosity of 2.50 dl / g.
[0087] [Polyimide film preparation example 1] The polyamic acid solution A was applied onto a mirror-finished stainless steel endless continuous belt (coating width 1240 mm) as a support for preparing a polyimide film using a die coater, and dried for 10 minutes at 90 to 115° C. The polyamic acid film, which became self-supporting after drying, was peeled off from the support and both ends were cut to obtain a green film. The obtained green film was transported by a pin tenter so that the final pin sheet spacing was 1140 mm, and was heat-treated at 170°C for 2 minutes in the first stage, 230°C for 2 minutes in the second stage, and 350°C for 6 minutes in the third stage.It was then cooled to room temperature over 2 minutes, and the poorly flat portions at both ends of the film were cut off with a slitter.The film was then wound up into a roll to obtain polyimide film 1A shown in Table 1. Similarly, the polyamic acid solution was changed to polyimide solution B or polyimide solution C, and the coating thickness on the support was changed to obtain polyimide films 1B and 1C shown in Table 1.
[0088] [Polyimide film preparation example 2] Polyamic acid solution A was applied to a polyimide film support having a surface roughness (Sa) of 1 nm, a maximum peak height (Sp) of 7 nm, and a peak density (Spd) of 20 / μm 2 The composition was applied to a polyester film having no coating layer on its surface using a comma coater (coating width: 1240 mm) and dried for 10 minutes at 90 to 115° C. After drying, the polyimide film (containing 10% by weight of solvent) became self-supporting, and was peeled off from the support and both ends were cut to obtain a green film. The obtained green film was conveyed by a pin tenter so that the final pin sheet interval was 1140 mm, and was heat-treated at 170°C for 2 minutes in the first stage, 230°C for 2 minutes in the second stage, and 350°C for 6 minutes in the third stage to remove the solvent. It was then cooled to room temperature in 2 minutes, and the poorly flat portions at both ends of the film were cut off with a slitter and wound up into a roll to obtain polyimide film 2A shown in Table 1. Similarly, polyimide films 2B and 2C shown in Table 1 were obtained by changing the polyamic acid solution to polyimide solution B or polyimide solution C and by changing the coating thickness on the support.
[0089] [Polyimide film preparation example 3] Polyamic acid solution A was applied to a polyimide film support having a surface roughness (Sa) of 3 nm, a maximum peak height (Sp) of 12 nm, and a peak density (Spd) of 25 / μm 2 The following unstretched polypropylene film was coated with a comma coater (coating width 450 mm) and dried at 85 to 105 ° C for 30 minutes to obtain a bilayer film of a support and a polyamic acid film (containing about 8% by mass of solvent). Next, the bilayer film was simultaneously stretched 2.8 times in the MD direction by utilizing the difference in peripheral speed of the rolls. The rolls were arranged so that the rolls did not contact the polyamic acid film side of the bilayer film between the rolls with the difference in peripheral speed. After stretching in the MD direction, both ends of the bilayer film were held by a clip tenter, and the film was conveyed while being heat-treated at 150 ° C so that the final pin sheet interval was 1140 mm, that is, the film was stretched 2.5 times in the TD direction, and then the polyimide film was peeled off from the support of the bilayer film, and further heat-treated at 350 ° C for 3 minutes to remove the solvent. Then, the film was cooled to room temperature in 2 minutes, and the parts of the film with poor flatness at both ends were cut off by a slitter and rolled up into a roll to obtain polyimide film 3A shown in Table 1. Similarly, the polyamic acid solution was changed to polyimide solution B or polyimide solution C, and the coating thickness on the support was changed to obtain polyimide films 3B and 3C shown in Table 1.
[0090] <Preparation of Laminate> Example 1
[0091] First, the polyimide film 1A obtained in Preparation Example 1 was cut to a width of 1090 mm x 1240 mm. Next, the film surface was treated by irradiating it with UV / O3 for 3 minutes using a UV / O3 irradiator (SKR1102N-03 manufactured by LAN Technical). The distance between the UV / O3 lamp and the film was 30 mm.
[0092] Using the device shown in the schematic diagram in Figure 1, a G5 size (1100 mm x 1250 mm, 0.7 mm thick glass substrate: Nippon Electric Glass Co., Ltd. OA10G) was coated with 3-aminopropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., KBM-903) as a silane coupling agent using a spray coater. The glass substrate was washed with pure water, dried, and then irradiated with a UV / O3 irradiator (LAN Technical Co., Ltd. SKR1102N-03) for 1 minute to dry clean.
[0093] The glass substrate thus coated with the silane coupling agent was set on a roll laminator equipped with a silicone rubber roller, and first, 500 ml of pure water was dropped using a dropper onto the surface coated with the silane coupling agent so that the water-based medium was spread over the entire substrate, wetting the substrate.
[0094] Next, the surface-treated surface of the polyimide film was placed on the silane coupling agent-coated surface of the glass substrate, i.e., the surface wetted with pure water, and the glass substrate and the polyimide film were laminated by pressing the polyimide film and the glass substrate while pushing out the pure water between them with a rotating roll from one side of the glass substrate, to obtain a provisional laminate. The laminator used was a laminator manufactured by MCK Corporation with an effective roll width of 1350 mm, and the lamination conditions were air source pressure: 0.5 MPa, lamination speed: 50 mm / sec, roll temperature: 22°C, environmental temperature 22°C, and humidity 55% RH. The obtained provisional laminate was heat-treated in a clean oven at 200° C. for 10 minutes to obtain a laminate of the present invention. The evaluation results of the obtained laminate are shown in Table 2.
[0095] (Examples 2 to 9, Comparative Example 1) Similarly, laminates were prepared under the conditions shown in Table 2, and the properties of the laminates were evaluated. The results are shown in Table 2.
[0096] (Examples 10 to 18, Comparative Example 2) Similarly, laminates were prepared under the conditions shown in Table 3, and the properties of the laminates were evaluated. The results are shown in Table 3.
[0097] [Table 1]
[0098] [Table 2]
[0099] [Table 3]
[0100] In the table, SCA: Silane coupling agent, Glass: Nippon Electric Glass OA10G Inorganic substrate size (glass size) G5 size (1100mm x 1250mm) aqueous medium Pure water: ultra pure water Pure water + MeOH: Pure water 99 / methanol 1 (mass ratio) It is.
[0101] <Application Example> Using the laminate obtained in Example 9, a tungsten film (75 nm thick) was formed on a polyimide film by vacuum deposition in the following steps, and a silicon oxide film (150 nm thick) was then laminated as an insulating film without exposure to air. Next, a silicon oxynitride film (100 nm thick) was formed as a base insulating film by plasma CVD, and an amorphous silicon film (54 nm thick) was then laminated as a base insulating film without exposure to air.
[0102] Next, in order to remove hydrogen elements from the amorphous silicon film and promote crystallization, a heat treatment was performed at 500° C. for 40 minutes to form a polysilicon film. The resulting polysilicon film was used to fabricate TFT elements. First, the polysilicon thin film was patterned to form silicon regions of a specified shape, and then a gate insulating film was formed, a gate electrode was formed, source and drain regions were formed by doping the active region, an interlayer insulating film was formed, source and drain electrodes were formed, and an activation process was performed to fabricate an array of P-channel TFTs using polysilicon. The polyimide film was burned off with a UV-YAG laser along the inner side of the circumference of the TFT array by about 0.5 mm, and peeled off by scooping up the edge of the cut with a thin razor blade, obtaining a flexible A3 size TFT array. Peeling was possible with very little force, and it was possible to peel off the TFT without damaging it. The obtained flexible TFT array maintained good characteristics without any deterioration in performance even when wrapped around a 3 mm diameter round rod. [Industrial Applicability]
[0103] As described above, the method for producing a laminate of the present invention and the laminate obtained therefrom can achieve a stable, uniform low adhesive strength even over a large area, and the occurrence of blister defects is extremely low. As a result, the laminate is extremely useful as a temporary support substrate for producing high-quality, large-area flexible devices.
Claims
1. A method for producing a laminate comprising, in this order, an inorganic substrate, a silane coupling agent layer, and a polyimide film having a yellow index of 10 or less, a light transmittance at a wavelength of 400 nm of 70% or more, a tensile modulus in both MD and TD of 3 GPa or more, and a CTE in both MD and TD of -5 ppm / °C to +55 ppm / °C, wherein the initial adhesive strength measured by a 90-degree peel method when peeling the polyimide film from the laminate is 0.06 N / cm or more and 0.20 N / cm or less (excluding the case where there is a portion where the initial adhesive strength measured by a 90-degree peel method when peeling the polyimide film from the laminate exceeds 0.25 N / cm), (1) applying a silane coupling agent to at least one surface of an inorganic substrate; (2) wetting either or both of the silane coupling agent-coated surface of the inorganic substrate and the adhesive surface of the polyimide film with an aqueous medium; (3) a step of laminating a polyimide film on the silane coupling agent-coated surface of the inorganic substrate; (4) a step of pressing the silane coupling agent-coated surface of the inorganic substrate and the adhesive surface of the polyimide film together while squeezing the aqueous medium out from between them; A method for producing a laminate, comprising:
2. (1) applying a silane coupling agent to at least one surface of a heat-resistant polyimide film; (2) Wetting either or both of the adhesive surface of the inorganic substrate and the silane coupling agent-coated surface of the polyimide film with an aqueous medium; (3) a step of superposing a silane coupling agent-coated surface of a heat-resistant polyimide film on the inorganic substrate; (4) a step of pressing the adhesive surface of the inorganic substrate and the silane coupling agent-coated surface of the polyimide film together while extruding the aqueous medium from between them; The method for producing a laminate according to claim 1, characterized in that the method comprises at least the steps of:
3. 3. A method for producing a flexible device, comprising a step of forming a functional element on a surface of the polyimide film of the laminate obtained by the production process according to claim 1, opposite to the bonding surface of the polyimide film to the inorganic substrate.
Citation Information
Patent Citations
Tankasuisononetsubunkaiho
JP1976052104A
photocell
JP1978004490A
Automatic paper supplying apparatus
JP1980031781A
Manufacturing method for color filter
JP2003121627A
Laminate, electronic device and method for manufacturing flexible electronic device
JP2017124587A